"Acquired" NKG2D Ligand Stimulates NK Cell–mediated Tumor Immunosurveillance. Issue 6 (July 2019) - Wang, Dongfang; Gu, Xiuling; Liu, Xinjun; Liu, Xiaoman; Wang, Bin; Lao, Fengxue; Fang, Min
Abstract : Engagement of activating receptor NKG2D to its ligand mediates natural killer (NK) cell activation and enhances cytotoxicity. NKG2D ligands (NKG2DLs) are frequently expressed on the tumor cell surface. However, the expression patterns of different NKG2DLs vary between tumor cells. Downregulation of certain ligand enables the tumor cells to escape NK cell–mediated immunosurveillance. By generating tumor cell lines with high expression of NKG2D ligand MULT1, we aimed to explore the function of NKG2DLs diversity on the activation and regulation of NKG2D signaling pathway. NK cells were potently activated by the "acquired" MULT1 expression on MOVCAR 5009 cells. Further, the progression of the tumor was significantly inhibited in mice inoculated with MULT1-expressing MOVCAR 5009 cells. Also, the pulmonary metastasis of MULT1-expressing B16-F0 cells was also significantly reduced in vivo. Our results implied that "acquired" NKG2D ligands enhance antitumor responses of NK cells, providing insights for designing novel therapeutic strategies and drugs to enhance NK cell surveillance over malignances.